Epidemiological characteristics of five non-COVID respiratory viruses among 37,139 all-age patients during 2018 − 2023 in Weifang, China: a cross-sectional study - Yining Quan; Xiaomeng Zhang; Guimao Yang; Chunqiang Ma; Mengmeng Liu (BMC Infectious Diseases)
Abstract Background Common non-COVID respiratory viruses, such as influenza virus (IFVA/IFVB), parainfluenza virus (PIV), respiratory syncytial virus (RSV), and adenovirus (ADV), often cause acute respiratory infections (ARIs). This study aimed to explore the epidemiological characteristics of these five viruses in patients with ARIs before, during, and after the COVID-19 pandemic from 2018 to 2023. Methods A total of 37,139 serum specimens and epidemiological data from all-aged patients who presented with ARIs were collected from January 2018 to December 2023. The IgM antibodies of five non-COVID respiratory viruses were tested by an IgM kit with indirect immunofluorescent assay (lFA). Results 12,806 specimens were screened as positive for any one of the targeted viruses, with an overall positivity rate of 34.48%. Among all age groups, the most prevalent respiratory viruses were PIV (21.30%) and influenza virus (17.30% of IFVB and 9.91% of IFVA). Children aged 1–14 years were most vulnerable to lower respiratory viruses, and children aged 4–6 years have the highest prevalence no matter the positivity rate for overall viruses (53.06%) or for each virus. From 2018 to 2023, the annual percentage change (APC) revealed that the prevalence of total viruses have a 13.53% rise (p < 0.05), which increased with statistically significant for all age groups. In addition, both the infection rate and the number of samples detected have decreased significantly in the “first-level response” stage of the COVID-19 pandemic and in the “first three months” after fully lifted. Compared to those in the previous five years, the total infection rate (44.64%) and infection rate (26.93%) of the older adults (> 60 years) were all the highest in 2023, and the number of samples collected in 2023 sharply increased, increasing by 77.10% compared to the average of the number of detected in 2018–2022. Conclusions The data from this study indicate that the epidemiological characteristics of five non-COVID respiratory viruses are vulnerability to the environment, age, sex, and epidemics status among AIR patients, and that the detected number and positivity rate of these viruses have increased in the “post-pandemic era”, which is critical for the late or retrospective diagnosis and can serve as a useful surveillance tool to inform local public policy in Weifang, China.